1966
DOI: 10.1063/1.1754537
|View full text |Cite
|
Sign up to set email alerts
|

FREQUENCY LOCKING AND DYE SPECTRAL HOLE BURNING IN Q-SPOILED LASERS

Abstract: A selfconsistent approach to spectral hole burning in quantum wire lasers Synchronously pumped modelocked dye laser pumped by a frequencydoubled modelocked and Q switched diode laser pumped Nd:YAG laser

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1969
1969
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Saturable filters were first employed in laser systems as Q-switching devices (Soffer 1964, Kafalas et a1 1964. In experiments with ruby and Nd : silicate lasers, spectral narrowing and even single-mode operation were sometimes observed (Sooy 1965, Hercher 1965, Soffer and McFarland 1966, while other authors reported spectral broadening and the generation of mode-locked pulse trains (Mocker and Collins 1965, DeMaria et a1 1966b, Stetser and DeMaria 1966. The type of behaviour depends on the absorber relaxation time in relation to the cavity transit time, as well as to its location in the cavity.…”
Section: Introductory Remarksmentioning
confidence: 93%
“…Saturable filters were first employed in laser systems as Q-switching devices (Soffer 1964, Kafalas et a1 1964. In experiments with ruby and Nd : silicate lasers, spectral narrowing and even single-mode operation were sometimes observed (Sooy 1965, Hercher 1965, Soffer and McFarland 1966, while other authors reported spectral broadening and the generation of mode-locked pulse trains (Mocker and Collins 1965, DeMaria et a1 1966b, Stetser and DeMaria 1966. The type of behaviour depends on the absorber relaxation time in relation to the cavity transit time, as well as to its location in the cavity.…”
Section: Introductory Remarksmentioning
confidence: 93%
“…Certains auteurs [26,32,34] ont realise d'ingénieuses experiences dont le resultat ne s'explique simplement que si le spectre d'absorption pendant la saturation presente un trou a la longueur d'onde excitatrice (« hole burning & # x 3 E ; & # x 3 E ; ) . Si cet effet ne nous parait pas avoir d'importance dans les phtalocyanines, il nous parait probable dans certaines cyanines (cryptocyanine) ou le temps de vie T1 est tres faible ( 10'1° s), ce qui n'est pas infiniment grand par rapport au temps de thermalisation (10-12, 10-13 s).…”
Section: Intervention De Niveaux Tripletsunclassified
“…In 1968 the inhomogeneous broadening [31,32] and in 1987 the photophysical hole burning (PPHB) [33,34] was observed in the liquid phase at room temperature in ns-measurements. Cross sections and population densities may then differ from the common values by 3-4 orders of magnitude [35].…”
Section: Introductionmentioning
confidence: 96%